Entre propostas e práticas : a implementação dos pressupostos teórico-metodológicos enunciativo-discursivos dos documentos norteadores nas aulas de língua portuguesa - Piottrowski, Juliana Márcia (2022)
The theme of this study is the implementation of the theoretical-methodological assumptions of the guiding documents in Portuguese Language (LP) classes in the 9th year of Elementary School (EF) and its general objective was to verify if and how the enunciative-discursive conception(s) established in the theoretical methodological references of the Parâmetros Curriculares Nacionais (PCNs), from 1998, Referencial Curricular Lições do Rio Grande, from 2009, Base Nacional Comum Curricular (BNCC), from 2018, Referencial Curricular Gaúcho (RCG), from 2018, and the Currículo de Referência do Território Municipal (CRTM), from 2019, are implemented by LP teachers. The theoretical bases were anchored in the theory of genres by Bakhtin and his Circle (2006, 2011, 2016) and of (multi)literacies in LP, according to Cope and Kalantzis (2000), Rojo (2012, 2015), Soares (2004, 2016) and Kleiman (2005, 2007). Regarding the conjectured hypotheses, it is highlighted that the partial or total implementation of the assumptions distilled from the guiding documents in the teaching practice of PL was foreseen. As for the methodology, the proposal is divided into two parts and presents, at the beginning, the documentary research, in which the theoretical-methodological conceptions that underlie the aforementioned guiding documents were explored. Having apprehended these assumptions, identified as enunciative-discursive, they were subsequently deepened through theoretical research based on the aforementioned authors. The second part focuses on a case study with two 9th grade LP teachers from Alpestre, one from the state public network, and the other, from the municipal network. In this sense, three instruments were applied for data collection: (i) questionnaire, with 10 questions, covering the assumptions specified in the documentary research; (ii) narrative interview, with 4 questions, related to the pedagogical work with the 4 language practices; and (iii) analysis of class records, which cover a period of the second two months of 2022 and add up to 10 records from Researched 1 and 16 releases from Researched 2, to verify if and how the enunciative-discursive conception(s) established in the theoretical-methodological references of the guiding documents are implemented in the LP teaching work operated by the teachers. From data analysis, in particular, it is important to highlight the main conclusions, resulting from the triangulation of the instruments, scrutinized, before that, in the light of the categories of analysis knowledge, perception, use/application and evaluation that the teachers have of the listed assumptions of beforehand. Based on the fact that the respondents know the guiding documents in their content, with emphasis on their methodological guidelines, it should be noted that the teachers base their didactic framework on the development of linguistic skills and abilities, along with what the BNCC proclaims. However, the improvement of such aptitudes with the students has different enunciative-discursive gradations in each language practice. Thus, reading and oral production appear to be imbued with the perspective advocated by the guiding documents, as they have texts related to their production contexts as their work center; linguistic/semiotic analysis, likewise, is based on practices in which grammar (and other semioses, to a lesser extent) must be understood in its functioning - in texts; the written production, in turn, does not include, at a certain level, in the sampling, some discursive aspects of its interlocution character.